1997
DOI: 10.1557/jmr.1997.0343
|View full text |Cite
|
Sign up to set email alerts
|

Spinel solid solutions in the systems MgAl2O4–ZnAl2O4 and MgAl2O4–Mg2TiO4

Abstract: Phase relations in two binary systems MgAl 2 O 4 -ZnAl 2 O 4 and MgAl 2 O 4 -Mg 2 TiO 4 have been studied and phase diagrams for them have been constructed. Based on the data of x-ray phase and crystal-optical analyses, the formation of a continuous series of solid solutions with spinel structure between the terminal members of the systems studied has been established. In the MgAl 2 O 4 -ZnAl 2 O 4 system the solid solution is stable in the range from room temperature to melting temperature. In the MgAl 2 O 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
33
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 7 publications
5
33
0
Order By: Relevance
“…Namely, the fully developed MgTiO 3 phase in our experiments was detected in the 10 h milled sample after its post-anneal treatment for 1 h at 900 • C; whereas, in the case of Mg 2 TiO 4 phase post-anneal processing at 1200 • C lasted only 1 h. However, in the latter case besides the dominant Mg 2 TiO 4 phase in the sample appeared also a small amount of the MgTiO 3 phase. Presumably, the latter effect was a consequence of the thermodynamic instability of Mg 2 TiO 4 phase, also observed earlier [30,31]. 3.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Namely, the fully developed MgTiO 3 phase in our experiments was detected in the 10 h milled sample after its post-anneal treatment for 1 h at 900 • C; whereas, in the case of Mg 2 TiO 4 phase post-anneal processing at 1200 • C lasted only 1 h. However, in the latter case besides the dominant Mg 2 TiO 4 phase in the sample appeared also a small amount of the MgTiO 3 phase. Presumably, the latter effect was a consequence of the thermodynamic instability of Mg 2 TiO 4 phase, also observed earlier [30,31]. 3.…”
Section: Resultssupporting
confidence: 70%
“…We would like to point out here that this phenomenon presumably is a consequence of the thermodynamic stability of the spinel Mg 2 TiO 4 . Namely, it is known that this phase starts to decompose to MgTiO 3 plus MgO phases below some temperature chosen from the range 1000-1400 • C [30,31]. Finally, it is evident that in the milled samples were incorporated a minor amount of the WC impurity-phase which appeared as a consequence of the contamination effect of the milling assembly (a wearing-off or abrasion effect).…”
Section: Resultsmentioning
confidence: 99%
“…The density reported in Fig. 1 [18] pointed out that a stable solid solution is possible between similar structured MgAl 2 O 4 and Mg 2 TiO 4 . A previous investigation [8] revealed that presence of a low melting phase formed at the grain boundary during excess doping of TiO 2 caused micro cracks, which could degrade the densification of spinel.…”
Section: Resultsmentioning
confidence: 86%
“…Second phase was not observed in our experiments. Petrova et al [14] proposed the following thermal decomposition mechanism to explain the formation of the MgTiO 3 phase.…”
Section: Resultsmentioning
confidence: 99%